2022
DOI: 10.1021/acsmaterialslett.2c00854
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin Zn2GeO4 Nanoribbons: Facile Synthesis and Selective Photocatalytic CO2 Reduction toward CO

Abstract: Atomically thin Zn 2 GeO 4 (ZGO) nanoribbons exclusively exposing the {100} facet of ∼1 nm in thickness were successfully prepared via convenient photo-oxidation exfoliation of the ZGO−ethylenediamine hybrid at room temperature. The ultrathin ZGO nanoribbons [abbreviated as ZGO(100)] exhibit efficient and dominantly selective CO 2 photoreduction performance into CO with the evolution yield of up to 20.81 μmol g −1 h −1 in the presence of water vapor, in much contrast to only CH 4 production of 0.67 μmol g −1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The former was assigned to the COO − species [36][37][38]. Numerous reports revealed that COOH * was the important intermediate for the CO product, which converted to * CO by accepting coupled proton and electron with releasing one H 2 O molecule [8,39,40]. The latter was due to the symmetric vibration of a bidentate CO 3 2− (v s (OCO)), commonly formed by the reaction of CO 2 with dual sites of surface oxygen and metallic atoms [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former was assigned to the COO − species [36][37][38]. Numerous reports revealed that COOH * was the important intermediate for the CO product, which converted to * CO by accepting coupled proton and electron with releasing one H 2 O molecule [8,39,40]. The latter was due to the symmetric vibration of a bidentate CO 3 2− (v s (OCO)), commonly formed by the reaction of CO 2 with dual sites of surface oxygen and metallic atoms [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…To date, certain achievements have been made in improving the conversion efficiency based on photocatalyst development through hybrid semiconductors, morphology regulation, and surface modification [4][5][6]. However, current investigations were focused on the high-concentration system, which highly relied on the processes involving capture, sequestration, and transport that consumed time, labor, and energy [7,8]. Considering the nature photosynthesis, it is vital to develop an advanced photocatalyst with a stable ability to deal with the CO 2 reduction reaction (CO 2 RR) with low concentration direct from natural air.…”
Section: Introductionmentioning
confidence: 99%
“…DFT reveals that the formed CO* is inclined to escape from the exclusively exposed (100) facet other than further protonation, leading catalytically selective CO production. [66] The high-index facets possesses a high density of surface steps and kinks with low-coordination numbers, which may exhibit extraordinary photocatalytic performance. [93] NH 2 -MIL-125(Ti) with exposed high-index (112) facets displays superior activity for CO 2 -to-CO and CH 4 conversions, which are 33 and 31 times higher for CO and CH 4 productions than the (001)/(111) facets.…”
Section: Facet Engineeringmentioning
confidence: 99%
“…DFT reveals that the formed CO* is inclined to escape from the exclusively exposed (100) facet other than further protonation, leading catalytically selective CO production. [ 66 ]…”
Section: Construction Of Active Sites For Selectively Photocatalytic ...mentioning
confidence: 99%
“…A series of intricate chemical processes is indispensable to convert CO 2 and realize turning "waste" into a treasure. At present, CO 2 reduction reaction (CO 2 RR) products can be divided into CO, [5][6][7][8] CH 4 , [9][10][11] CH 3 OH, [12][13][14] HCOOH, [15][16][17] C 2 H 4 , [18][19][20][21] C 2 H 5 OH 22 , and some other chemical compounds 23,24 according to the types of catalysts. Among them, C 2 H 4 has garnered significant attention from researchers for its versatility and usefulness as a raw material in the synthesis of many chemicals.…”
Section: Introductionmentioning
confidence: 99%